Analysis Of Registration Workforce Needs Based On The Wisn Method At Assalam Gemolong General Hospital - Novratilova, Sinta; Pradista, Nur Adi Satriyo; Widiyanto , Wahyu Wijaya (Medicor : Journal of Health Informatics and Health Policy, 2024)
There are 8 officers at the registration section of the Assalam Gemolong General Hospital. Activities in one shift not only serve the registration of RJ, RI and IGD patients but also find and retrieve medical record documents to the filing rack, after that officers still submit medical record documents to the polyclinic and ER. On Mondays, Tuesdays, Thursdays and Saturdays many patients go to Assalam Gemolong General Hospital for treatment, so that the registration officer has difficulty in patient registration services. As a result, patient queues will pile up because there are only 3 registration counters. The method used is the WISN method with available working time stages, workload standards, allowance standards and labor requirements. The research sample was 8 registration officers. Research instruments in the form of observation guidelines, interview guidelines, stopwatches, calculators, stationery. The results showed that the available working time was the morning shift for registration of RJ, RI and IGD 117,600 minutes, the afternoon shift for registration of RJ, RI and IGD 100,800 minutes and the night shift for registration of the IGD and RI 194,700 minutes for hospitalization. The registration officer's work unit consists of 3 high school graduates and 5 medical record graduates. The standard workload of registration for morning shifts is RJ and IGD 10,556.55 minutes/year and registration for RI 7,829.56 minutes/year, registration for evening shifts for RJ and IGD is 9,048.47 minutes/year and registration for RI 6,711.05 minutes/year and registration for night IGD shifts 17,447.55 minutes/year and RI Registration 12,962.71 minutes/year. The standard allowance for the morning shift is 1.146, the day shift is 1.4 and the night shift is 0.23. The need for labor requires additional registration personnel on the afternoon shift as many as 1 officer from 3 existing officers.